Economic Development of a Selected Region: Mathematical Modeling - Myšková Renáta; Linkeová Ivana (IGI Global, 2013)
Macro-economic aspects and further factors influence the economic development of a region. Two new indicators (Index of Citizens’ Financial Provision and Risk of Regional Economic Development) are introduced in this paper. These indicators enable people to evaluate the financial provision of citizens and the economic risk of a region in more detail. To demonstrate a function of these new indicators in economic practice, the authors focus on the selected region (Vysočina, Czech Republic) due to the following specific characteristics. Economic performance of the Vysočina Region in comparison with other regions of the Czech Republic is below the average. When calculating GDP per capita the Vysočina Region ranks eleventh position from fourteen regions in the Czech Republic. The input data for examples given in this paper are based from the Czech Statistical Office. Mathematical modeling of the new developed indicators has been created in Microsoft Excel program. To design Indicator Risk of Regional Economic Development the fuzzy sets logic has been used.
Ekonomický rozvoj vybraného regionu: matematické modelování
Keywords: citizens; economic development; economic practice; financial provision; indicators; region; obyvatelé; ekonomický rozvoj; ekonomická praxe; finanční zajištění; indikátory; region